Cholangiocarcinoma Metastasis to the Spine and Cranium - Hanna, Joshua A. (Ochsner J, 2020)
Background: Cholangiocarcinoma (CCC), a rare tumor arising from the viscera, has a poor prognosis. Although CCC is prone to metastasis, spread to the cranium and spine is exceedingly rare. Treatment for metastatic disease is palliative, with total resection of the primary lesion the only cure. We describe a case of metastatic CCC to the spine and cranium treated with surgical resection. Case Report: A 61-year-old male with a history of hepatitis C with liver transplant and incidental discovery of CCC presented with gradually increasing back pain. Physical examination revealed a palpable nontender mass in the parieto-occipital area. Computed tomography survey of the spine and head revealed mixed sclerotic and lytic lesions of the T9, T11, L2, and L5 vertebral bodies, a lytic lesion on the T6 vertebral body, and a 1.4-cm lesion in the right occipital calvarium. The patient underwent right occipital craniotomy for excisional biopsy of the calvarial mass with gross total resection and immunohistochemical confirmation of CCC. The patient was started on gemcitabine chemotherapy and radiation therapy for spinal metastases. Three months later, the patient died from metastatic disease complications. Conclusion: To our knowledge, only 6 cases of cranial CCC have been reported, and only 2 reported mixed cranial/spinal involvement. We report a rare case of CCC metastasis to the spine and cranium that was treated with surgery, chemotherapy, and radiotherapy. CCC should be considered an exceedingly rare etiology with treatment options aimed solely at palliation. This case supplements the existing literature to inform medical and surgical decision-making.